Horizontal Bulk Material Pressure in Silo Subjected to Impulsive Load - Radosław Tatko; Sylwester Kobielak (Shock and Vibration)
This paper describes laboratory tests carried out in the steel flat-bottomed silo model filled with sand, subjected to external dynamic loads. The model was placed on a system of springs, which represent subsoil. The loads in the form of horizontal impulses were applied to the bottom plate of the silo. Horizontal pressure-time courses were used to analyze the influence of subsoil vibrations on the distribution changes of these pressures. Basic conclusion: (1) the subsoil vibrations cause two types of changes of the horizontal pressures: stable changes which are observed when the model vibrations finish and cyclic of short duration (brief) changes; (2) the subsoil vibrations either generate stable increase or stable decrease of the pressures from before vibrations or do not generate any essential stable change; (3) the cyclic dynamic changes of the horizontal pressures depend on the direction of the silo wall displacements and they are the function of the values of these displacements.